Pendekatan Penghidupan Berkelanjutan untuk Mendukung Rumah Tangga Budidaya Perikanan di Tengah Pergeseran Struktural di Kabupaten Sidoarjo - Herman Cahyo Diartho; Mery Cindio Elan; Aisah Jumiati (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study examines the role of the Sustainable Livelihood Approach (SLA) in supporting aquaculture households in Sidoarjo Regency as they adapt to structural shifts driven by industrialization and urbanization. The research analyzes how sustainable livelihood strategies enhance the economic stability of pond-based households impacted by land-use change. Using a quantitative approach with descriptive analysis, the study employs Structural Equation Modeling Partial Least Squares (SEM-PLS) to evaluate the influence of key variables. Conducted in Kalisogo Pond Village, the study uses purposive sampling based on criteria such as economic reliance on aquaculture and sector experience. Data were gathered through questionnaires and analyzed for model validity and reliability. Findings indicate that the SLA significantly bolsters pond households’ adaptive capacity to structural shifts. Income diversification through non-aquaculture activities enhances economic stability and reduces dependence on pond farming. Social capital further supports households by strengthening local community networks. The study underscores the importance of institutional backing and microcredit access for aquaculture households. Policymakers and financial institutions are encouraged to support sustainable adaptation measures. These findings offer valuable insights into the SLA’s application amid structural changes in industrialized coastal regions.